2014
DOI: 10.1080/13607863.2014.977769
|View full text |Cite
|
Sign up to set email alerts
|

What prevents old people living alone from feeling lonely? Findings from the KORA-Age-study

Abstract: Absence of depression and a functioning social network are the most important protecting resources against loneliness for elderly people living alone, while income, level of education and age-related limitations have no impact. These findings should be considered when supporting the elderly in successful aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 40 publications
3
39
0
4
Order By: Relevance
“…A previous study by Victor et al [43] showed that older women living alone were more likely than those with others to experience feeling of social isolation partly because of a lack of social network including emotional support. Improved social relationships were connected with reduced level of loneliness [43] which was associated with depression [44, 45]. Compared to community involvement, individual relationship is more informal and therefore older women living alone can be dependent principally on individual relationship for emotional support.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study by Victor et al [43] showed that older women living alone were more likely than those with others to experience feeling of social isolation partly because of a lack of social network including emotional support. Improved social relationships were connected with reduced level of loneliness [43] which was associated with depression [44, 45]. Compared to community involvement, individual relationship is more informal and therefore older women living alone can be dependent principally on individual relationship for emotional support.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that while living alone does not necessarily increase psychological distress in old age (Stone et al 2013), the lack of goals related to activities or relationships could well do so (Lou and Ng 2012). The absence of meaningful social goals might also increase the risk for loneliness among people living alone (Zebhauser et al 2015). Thus, the possibilities for goal setting among older people living alone merit further consideration.…”
Section: Discussionmentioning
confidence: 99%
“…A previous KORA Age study demonstrated that a stressful life event was not associated with loneliness in older people, yet depression and social network were (Zebhauser et al, 2014). In the current study, the association between high oxytocin, attachment and suffering from an adverse life experience was independent and robust when models were controlled for depression, cognition and social network.…”
Section: Endogenous Oxytocin Is Associated With Reduced Stress Experimentioning
confidence: 96%
“…Participants were classified as physically active if they regularly participated in sports during leisure time ≥1 h/week in either season. Sensitivity analyses on a smaller sample due to missing values additionally considered potential modifying effects of depressed mood using the geriatric depression scale 15 (GDS15 with a cut off ≥5 indicating depressed mood) and the Beckman social network index with scores ranging from 1 to 4 with 3 and 4 combined to represent a high social network) as previously described (Zebhauser et al, 2014). Cognitive status was assessed by the Telephone Interview for Cognition Scale which ranged from18 to 52 after correction for years of education; normal cognition was assigned with scores between 32 and 52 as previously published (Lacruz et al, 2013).…”
Section: Confounding Variablesmentioning
confidence: 99%